Design considerations of high RAP-content asphalt produced at reduced temperatures - Abed, Ahmed; Thom, Nicholas; Lo Presti, Davide (Springer Verlag, 2018)
In many countries recycling of reclaimed asphalt pavement (RAP) for road surface layers is limited to a maximum of 10–30%. This is due to technical limitation of common asphalt plant but also to specifications that are still restrictive when it comes to increasing RAP in surface courses. The mistrust in this practice is mainly related to uncertainty in performance of these mixes as well as to existing fundamental issues with the mix design, especially when production temperatures are lowered. This paper analyses some of the factors affecting the design of warm asphalt mixtures for surface course layers containing 50% RAP, and suggests a framework to justify the common assumption of full blending by optimising production conditions. A control hot mix asphalt which was manufactured with 49 dmm penetration binder and asphalt mixtures containing 50% RAP produced at temperatures between 95 and 135 °C and at different mixing times were investigated in terms of volumetric properties, indirect tensile stiffness modulus, and indirect tensile strength. The high-content RAP mixtures were produced within the warm mix region by using only a very soft binder as a rejuvenator, which reduces production costs. Statistical analysis was deployed, and different models were developed to estimate degree of blending between RAP binder and rejuvenator binder, and to predict the equivalent penetration of the blend without binder extraction and recovery. The analysis results showed that the selected performance indicators correlate significantly with mixing time and temperature, and provide evidence that only in certain circumstances and if the production conditions are accurately controlled, the practical full blending approach is acceptable.